واقع الذكاء الاصطناعي في العملية التعليمية دراسة تقييمية لاداء اساتذة قسم اللغة والادب العربي بجامعة الشهيد حمه لخضر - مليك، جوادي; ولابي، ابتسام; خلايفة، زينب (University of Eloued جامعة الوادي, 2024)
تسعى الدراسة الحالية لإبراز مدى استخدام الذكاء الاصطناعي في العمليّة التعليمية، من طرف الأساتذة، ودوره فيها، والتعرّف على أهم تطبيقاته المستخدمة داخل الجامعة، وبالأخصّ قسم اللغة والأدب العربي، وفي الأداء الميداني. وقد تركّزت هذه الدراسة حول الإشكالية الآتية: كيف هو أداء أساتذة قسم اللغة والأدب العربي في مجال استخدام الذكاء الاصطناعي في العملية التعليمية؟ أمّا المنهج المعتمد في الدراسة هو المنهج الوصفي، كما تمّ اختيار عينة الأساتذة بقسم اللغة والأدب العربي بجامعة الشهيد حمه لخضر الوادي، هذا خلال السنة الدراسية: 2023/ 2024، بالإضافة إلى استخدام أدوات وأسّس جمع البيانات التالية: الملاحظة والمقابلة، والاستبيان، لجمع بيانات الدراسة، فقد استعملت النسبة المئويّة (%). وقد أفضت الدراسة إلى مجموعة من النتائج منها: - العناية بالذكاء الاصطناعي وتطبيقاته لدى الأساتذة متوسّطة، وليست بدرجة عالية. - أن ّالموضوع الجديد المطروح حول الذكاء الاصطناعي في الوسط الجامعي يحظى بنسبة متوسطة. - لم يتم عقد ندوات ومؤتمرات كافية لتوعية الأساتذة بالآثار الإيجابية حول هذا المجال. - وجدنا محاولات ضعيفة لتطوير أنظمة الدراسة بالنسبة لاستخدام تطبيق Chat Gpt. - ضعف الثقافة بقسم اللغة والأدب العربي حول إيجابيات الذكاء الاصطناعي Study Summary -The current study seeks to highlight the extent of the use of artificial intelligence in the educational process, by professors, and its role in it, and to identify its most important applications used within the university, especially the Department of Arabic Language and Literature, and in field performance - This study focused on the following problem: How is the performance of professors of the Department of Arabic Language and Literature in the field of using artificial intelligence in the educational process - The approach adopted in the study is the descriptive approach, and a sample of professors in the Department of Arabic Language and Literature at the University of Martyr Hama Lakhdar El Oued was se-lected during the academic year: 2023/2024, in addition to using the following data collection tools and foundations: observation, interview, and que tionnaire, to collect study data. I used the percentage(%). :The study led to a set of results, including - -The interest in artificial intelligence and its applications among professors is moderate, but not high. - The new topic proposed about artificial intelligence in the university community has an average percentage. - Not enough seminars and conferences were held to educate professors about the positive effects of this field. - We found weak attempts to develop study systems regarding the use of the Chat Gpt application. - Weak culture in the Department of Arabic Language and Literature about the positives of artificial intelligence.
371/ 001